Impact of Tower Grounding Resistance on Insulator Flashover Risk in 500 kV HVDC Transmission Systems under Lightning Strikes - Shirley, Rufus; Dayang Syahirah, Awang Shebli; Noor Azlinda, Ahmad; Noradlina, Abdullah; Nazreen, Junaidi; Sharifah Masniah, Wan Masra (2025)
High Voltage Direct Current (HVDC) transmission lines are vulnerable to lightning strikes, which can greatly affect tower performance. This study utilizes PSCAD electromagnetic transient simulations to analyze the transient behavior of a 500 kV HVDC tower under two lightning strike scenarios: (a) shielding wire, and (b) phase conductor. Both scenarios investigated the influence of varying tower grounding resistance and its effect on insulator flashover risk. The model incorporates realistic parameters for shielding wires, tower conductors, insulators, and back flashover. Detailed evaluation of the transient response reveals that increasing grounding resistance leads to higher induced voltage across insulators for both scenarios, consequently elevating the risk of flashover events. Optimal lightning protection is achieved when tower grounding resistance is maintained between 80–100 Ω. These findings highlight the critical role of effective grounding for reliable HVDC operation during lightning events.